GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA DI SMK 1 SUNGAI ROTAN - Fransiska, Cyntia; Nurfitriana, Nurfitriana; Saputri, Ana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Education in the era of industrial revolution 4.0 in the form of changes in the way of learning, thinking patterns and how students act in developing creative innovations in various fields. With this, it can reduce unemployment in Indonesia, especially in global market competition. The school literacy movement (GLS) began to be implemented by the government with the enactment of the Revised 2013 Curriculum, with the aim of forming students' character. This study aims to determine school preparation, implementation, and to know the obstacles faced by schools in implementing GLS. This study uses qualitative research. The location of the research is at SMK 1 Sungai Rotan. The subjects in this study were students of SMK 1 Sungai Rotan. Data collection techniques used are interviews. The results showed that the habitus literacy of students at Sungai Rotan 1  School was not fully formed because of the low interest in reading students.